Mitigating devastating diseases in vegetables - Chowdappa, P (Indian Horticulture, 2019)
The diseases caused by Phytophthora spp. have emerged as major production constraints for sustainable vegetable production in India. Since 2008, severe outbreaks of Phytophthora diseases such as late blight on tomato (P. infestans), fruit rot on brinjal and cucurbits (P. parasitica), foliar blights and wilts in chili (P. boehmeriae and P. capsici) have been noticed. The migration of 13_A2 genotype P. infestans from Europe is the cause of outbreaks of destructive late blight in India and this stresses the importance of bio-security in agricultural trade. The emergence of P. boehmeriae is responsible for severe leaf blight epidemics on hot pepper in south India, although it is not serious pathogen on any crop in any part of the world. These invasive and emerging Phytophthora species have epidemiological and management implications for production of vegetable crops in India.